2006
DOI: 10.1002/gps.1662
|View full text |Cite
|
Sign up to set email alerts
|

Old age mental health services in England: implementing the National Service Framework for Older People

Abstract: Three years after the publication of the NSFOP there remained significant gaps in services for older people with mental health problems and substantial variation in provision between districts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 24 publications
(29 reference statements)
0
58
1
Order By: Relevance
“…While some services had extensive integrated multidisciplinary teams, more than a third of teams had no ring-fenced social work time and several lacked consistent arrangements to co-ordinate the care of even their most needy clients. 34 The service in North West England in which the study reported in this paper was undertaken appeared typical of services nationwide. Serving a population of about 56 000 people aged 65 and over, small CMHTs, primarily staffed by qualified nurses and support staff, were based in each of the area' s main towns and worked a traditional Monday-Friday, 9am to 5pm pattern, complemented by day hospital provision, outreach services and inpatient beds.…”
Section: Characteristics Of Intensive Care Managementmentioning
confidence: 92%
See 2 more Smart Citations
“…While some services had extensive integrated multidisciplinary teams, more than a third of teams had no ring-fenced social work time and several lacked consistent arrangements to co-ordinate the care of even their most needy clients. 34 The service in North West England in which the study reported in this paper was undertaken appeared typical of services nationwide. Serving a population of about 56 000 people aged 65 and over, small CMHTs, primarily staffed by qualified nurses and support staff, were based in each of the area' s main towns and worked a traditional Monday-Friday, 9am to 5pm pattern, complemented by day hospital provision, outreach services and inpatient beds.…”
Section: Characteristics Of Intensive Care Managementmentioning
confidence: 92%
“…12,21,31,32 However, like many others, 34 the area in which this study was undertaken had neither an intensive care management service, nor multi-agency CMHTs. In order to meet the standards in Box 2 therefore, not only would qualified social work practitioners need to be integrated within existing CMHTs, but the community mental health nurses' remit would need to expand to incorporate the role of care manager in those cases where their specific expertise made them the most appropriate personnel to undertake this function.…”
Section: Care Management Should Be Provided By Members Of a Multidiscmentioning
confidence: 99%
See 1 more Smart Citation
“…A postal survey of older adult psychiatrists demonstrated significant gaps in these ser vices. 11 For instance, nearly a third of respondents reported a lack of access to separate wards for organic and functional illness and less than a quarter considered community care adequate. Psychosocial input was one resource identified as being in high demand.…”
Section: The Need For Crht Services For Older Peoplementioning
confidence: 99%
“…Many studies describe the biological as well as social and psychological characteristics of older people. In terms of function, there is great variety among older adults [3]. Proper nutrition, lifestyle, sport activities, and a calm emotional state are resilience factors for everybody, but they are more critical for older adults and thus influence the aging process [4].…”
Section: Introductionmentioning
confidence: 99%